2016
DOI: 10.1099/jgv.0.000451
|View full text |Cite
|
Sign up to set email alerts
|

A novel corneal explant model system to evaluate antiviral drugs against feline herpesvirus type 1 (FHV-1)

Abstract: Feline herpesvirus type-1 (FHV-1) is the most common viral cause of ocular surface disease in cats. Many antiviral drugs are used to treat FHV-1, but require frequent topical application and most lack well-controlled in vivo studies to justify their clinical use. Therefore, better validation of current and novel treatment options are urgently needed. Here, we report on the development of a feline whole corneal explant model that supports FHV-1 replication and thus can be used as a novel model system to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 34 publications
0
23
0
1
Order By: Relevance
“…For these experiments, we decided to use cidofovir, which is a topical nucleoside analogue commonly used to treat FHV-1-induced ocular disease with reported clinical efficacy based on a controlled in vivo experimental study (12, 24). We and others have previously determined the EC 50 of cidofovir for FHV-1 by using traditional plaque reduction assays and found the EC 50 to range between 7.9 and 21.5 µM (2527). To determine the EC 50 by ECIS, CRFK cells were infected with FHV-1 at an MOI of 0.01 and treated with decreasing concentrations of cidofovir at the time of infection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For these experiments, we decided to use cidofovir, which is a topical nucleoside analogue commonly used to treat FHV-1-induced ocular disease with reported clinical efficacy based on a controlled in vivo experimental study (12, 24). We and others have previously determined the EC 50 of cidofovir for FHV-1 by using traditional plaque reduction assays and found the EC 50 to range between 7.9 and 21.5 µM (2527). To determine the EC 50 by ECIS, CRFK cells were infected with FHV-1 at an MOI of 0.01 and treated with decreasing concentrations of cidofovir at the time of infection.…”
Section: Resultsmentioning
confidence: 99%
“…WT FHV-infected CRFK cells and isotype control antibodies (Abcam, Inc., Cambridge, United Kingdom) were included as controls. Cells were imaged exactly as previously described (27). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For flow cytometry, a recombinant FH2CS FeHV-1 strain (FeHV-1-gD-DsRed) was used, which we generated in house using clustered regularly interspaced short palindromic repeat (CRISPR)/Cas9 genome engineering to express DsRed Express 2 fused to the C-terminal end of glycoprotein D (48). All viral stocks were grown and their titers were determined on CRFK cells, as previously described (26). Raltegravir (ChemieTek, Indianapolis, IN) and acyclovir (Sigma-Aldrich, St. Louis, MO) were diluted in DMSO.…”
Section: Cells Viruses and Drugs Crfk Cells (American Typementioning
confidence: 99%
“…Like HHV-1, FeHV-1 has similar challenges for successful treatment (24,25). Our laboratory has shown previously that raltegravir can inhibit replication of FeHV-1, both in cell culture and in an ex vivo corneal explant model, comparably to the currently utilized antivirals (26). Furthermore, we recently demonstrated that raltegravir reduces FeHV-1 shedding duration and improves clinical outcomes in experimentally infected cats (C. B. Spertus, M. R. Pennington, G. R. Van de Walle, Z. I. Badanes, B. E. Judd, H. O. Mohammed, and E. C. Ledbetter, submitted for publication).…”
mentioning
confidence: 98%